Estimates of epilepsy prevalence, psychiatric co-morbidity and cost. (April 2023) - Christensen, Jakob; Dreier, Julie Werenberg; Sun, Yuelian; Linehan, Christine; Tomson, Torbjörn; Marson, Anthony; Forsgren, Lars; Granbichler, Claudia A.; Trinka, Eugen; Illiescu, Catrinel; Malmgren, Kristina; Kjellberg, Jakob; et al.
Highlights: The overall prevalence of epilepsy was 0.67%. The prevalence was 0.69% for males and 0.65% for females. Over time, epilepsy prevalence decreased in the young and increased in the elderly. Psychiatric co-morbidity in epilepsy was higher than previously reported (37.4%). Total annual individual net costs associated with epilepsy were €30, 683. Abstract: Purpose: This study estimated epilepsy prevalence, psychiatric co-morbidity and annual costs associated with epilepsy. Methods: We used Danish national health registers to identify persons diagnosed with epilepsy and psychiatric disorders, and persons using antiseizure medication and persons using drugs for psychiatric disorders. We calculated the prevalence of epilepsy and co-morbid psychiatric disorders in Denmark on December 31, 2016, using information on epilepsy and psychiatric disorders based on combinations of hospital contacts and use of antiseizure and psychoactive medication. Further, direct and indirect annual costs associated with epilepsy were calculated using individual-level data from a range of socioeconomic registers. Results: There were 5, 044, 367 persons alive and living in Denmark on December 31, 2016, including 33, 628 persons with at least one hospital contact with epilepsy in the previous five years (epilepsy prevalence 0.67% (0.69% males; 0.65% females)). Among these persons with epilepsy, we identified 12, 562 (37.4%) persons with a psychiatric disorder or use of drugs used for psychiatric disorders as compared with 801, 052 (15.9%) persons in the general population. The estimated total annual individual net costs associated with epilepsy was €30, 683. Compared with prevalence estimates on December 31, 2006, the prevalence of epilepsy on December 31, 2016, was slightly higher in the older population and slightly lower in children Conclusions: Population estimates from national registers provide epilepsy prevalence estimates of approximately 0.6–0.7% - similar to previous reviews of epilepsy prevalence. In addition, the national sample allowed idenitfication of high prevalence of psychiatric disorders and high societal costs associated with epielspy.